2023
DOI: 10.1002/jcaf.22607
|View full text |Cite
|
Sign up to set email alerts
|

Board gender diversity and the financial performance of Pakistani non‐financial firms: A fuzzy‐set QCA approach

Abstract: According to the upper echelon's theory, the decision-making process in regard to competitive strategies by the top management has an enduring impact on firm performance (Hambrick & Mason, 1984). Moreover, the attributes of the individuals in top management may also affect the decision-making process. The purpose of this research is to analyze the board gender diversity impact on the financial performance of the non-financial companies of Pakistan. Qualitative comparative analysis (QCA) is employed which is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
0
1
0
Order By: Relevance
“…As a result, there has been a rise in the number of studies examining the influence of women directors on various important factors. These include capital structure and financial distress García & Herrero (2021); Mansour et al (2022a); Mansour et al (2022b); Shubita (2023a), agency costs (Ain et al (2021), financial manipulation (Wahid, 2019), dividend payments Benjamin & Biswas (2019), firm efficiency , corporate social performance Jizi et al (2022); Lutfi et al (2023) and firm performance (Naz et al, 2023;Salloum et al, 2019). According to Pandey et al (2020), these results are also expected to apply to creditors and lenders in the corporate sector.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, there has been a rise in the number of studies examining the influence of women directors on various important factors. These include capital structure and financial distress García & Herrero (2021); Mansour et al (2022a); Mansour et al (2022b); Shubita (2023a), agency costs (Ain et al (2021), financial manipulation (Wahid, 2019), dividend payments Benjamin & Biswas (2019), firm efficiency , corporate social performance Jizi et al (2022); Lutfi et al (2023) and firm performance (Naz et al, 2023;Salloum et al, 2019). According to Pandey et al (2020), these results are also expected to apply to creditors and lenders in the corporate sector.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…However, it has been found that having women directors is a crucial determinant of effective governance in companies Alshirah et al (2023); Jizi et al (2022), particularly when it comes to their financing strategies (Naz et al, 2023). This is especially evident in decisions related to capital structure and borrowing costs Mansour et al (2023b); Miah et al (2023); Aksoy & Yilmaz (2023), as the presence of gender diversity can lead to robust plans that contribute to the long-term survival of companies in the market (Zattoni et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Still, studies on this matter have yielded conflicting results (Khan et al, 2023). Unlike industrialized nations like Norway, Spain, Italy, and Germany to name a few (Yu & Madison, 2021), where there are gender quotas in place, most developing countries (Unite et al, 2019) with fragile investor protection, like Jordan (Almarayeh, 2021), do not have rules or regulations requiring or encouraging WOCBs (Naz et al, 2023). So, there is a limited probe into the link between BGD and company performance in developing nations (Hazaea et al, 2023), which could be attributed to the scarcity of WOCBs (Mohsni et al, 2021).…”
Section: Introductionmentioning
confidence: 99%